2017
DOI: 10.1590/2317-1782/20172016081
|View full text |Cite
|
Sign up to set email alerts
|

Análise acústica do padrão entoacional da fala de indivíduos com Transtorno do Espectro Autista

Abstract: RESUMO Objetivo Analisar elementos prosódicos de segmentos da fala de escolares com transtorno do espectro autista (TEA) e comparar com grupo controle, por meio de uma análise acústica. Método Foram realizadas gravações da fala de uma amostra de indivíduos com TEA (n=19) e com desenvolvimento típico (n=19) do gênero masculino, intervalo: 8-33 anos. Para coleta de dados, utilizou-se como roteiro o questionário de prosódia do ALiB (Atlas Linguístico Brasileiro), que contém frases interrogativas, afirmativas e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 13 publications
1
16
0
15
Order By: Relevance
“…Hubbard and Trauner ( 2007 ) observed the range of vowel intensity (in repetition and spontaneous speech) and found significant variation between participants with and without autism. The same pattern was found for the intensity of elicited utterances (minimum, maximum, and range intensity) by Olivati et al ( 2017 ), whereas no difference on a mean intensity measure was reported by van Santen et al ( 2010 ) using the PEPS-C (Peppé and McCann 2003 ). Likewise, no consensus emerges from studies examining duration or flow rate (a.o.…”
Section: Language Profiles In Asdsupporting
confidence: 78%
See 1 more Smart Citation
“…Hubbard and Trauner ( 2007 ) observed the range of vowel intensity (in repetition and spontaneous speech) and found significant variation between participants with and without autism. The same pattern was found for the intensity of elicited utterances (minimum, maximum, and range intensity) by Olivati et al ( 2017 ), whereas no difference on a mean intensity measure was reported by van Santen et al ( 2010 ) using the PEPS-C (Peppé and McCann 2003 ). Likewise, no consensus emerges from studies examining duration or flow rate (a.o.…”
Section: Language Profiles In Asdsupporting
confidence: 78%
“…On the production side, pitch has been widely investigated, but there is no consensus regarding the indices that can effectively characterize the prosody of autistic individuals. Some studies found higher pitch measures than in neurotypical children (Chen et al 2021 ; Olivati et al 2017 ; van Santen et al 2010 ; a.o. ), while others reported results equivalent to those of neurotypical children (Dahlgren et al 2018 ; Diehl and Paul 2013 ; Hubbard and Trauner 2007 ; Paul et al 2008 ; a.o.).…”
Section: Language Profiles In Asdmentioning
confidence: 97%
“…Test sequences contain 30 speech samples, thus, the total number of speech fragments is 90 (45 fragments for TD and AD children each). The choice of children with ASD and DS is due to the specific features of their speech, which manifest themselves at different levels of organization of speech communication and behavior (Olivati et al, 2017, Bonneh et al, 2011, Kent, Vorperian, 2013Wolk, Brennan, 2016). When listening to audio tests, the subjects filled out specially designed questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Development, v. 9, n. 11, e92291110437, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.10437 Durante a terapia, as questões linguísticas são colocadas em prática, surgindo assim, dois fatores que os envolvem, o fator afetivo e a própria linguística. Respectivamente, a primeira, simboliza os aspectos não verbais da linguagem, sendo necessários na transmissão e reconhecimento da expressão, da emoção, como da alegria, raiva, tristeza, entre outras, consequente o segundo fator, simboliza os aspectos verbais, enfatizados pela compressão da leitura, da fala, da escrita (Olivati et al, 2017).…”
Section: Utilização Do Sistema Pecs Como Uma Comunicação Alternativaunclassified